Procesy polityczne członków zakonów męskich i kongregacji w Czechach w latach 1948–1989 - Vlček, Vojtěch (Pamięć i Sprawiedliwość, 2017)
The political trials of members of male orders and congregations in the Czechosloslovakia in the period of 1948–1989 The study depicts persecutions of male orders and congregations in the period of the Communism regime in the Czech lands during the period of 1948–1989. It indicates the graduał restriction of their activities after the Communist takeover in February 1948. The first part includes the period of 1948–1968, namely the mass attack of the Communist oppressors on the orders shortly after assuming authority, the restriction of their public activities until the complete liquidation of all male orders in Czechoslovakia in April 1950, the so-called K campaign implemented by the state security services (in Czech: Státní bezpečnost). It also mentions the life of monks in centralising internment camps and the illegal renewing of communes as well as the continuation of conventual life in hiding in the 1950s and 1960s. The most significant form of the persecutions committed on monks were the political show trials. In the early 1950s and subsequently in the 1960s, within the Czech lands, during two large rounds of trials, 361 monks were convicted in 175 trials, including 18 of them more than once. The frequent cause of the imprisonment and conviction of the monks was, firstly, their public activities, reading pastoral letters, criticising Communism during their sermons or helping people related to the Anti-Communism movement. In the late 1950s and early 1960s, in the majority of case, these were group trials including several dozen members of the order, the purpose of which was the liquidation of any signs of life emanating from the Order: secret meetings, enrolling new members, ordinations. In particular, the 1950s were characterised by severe sentences (58 monks were sentenced to 10-15 in prison, 14 to 20 years or more and 3 to life imprisonment). The most striking aspect was the cruelty of the interrogation methods of the secret agents of the state security, mentally and physically torturing the persons they interrogated; at least 3 monks died in remand centres and 6 while serving time in prison. The second part of the text provides an analysis of the orders in the period 1968–1989. The nationwide thaw in the period of the so-called Prague Spring in 1968 brought a short-term attempt at reviving conventual life in the Czech Republic. After the invasion of the Warsaw Pack military forces and progressing normalisation in the 1970s, conventual communes underwent a process of destruction at the hands of secret church officers and the state security services, while the existence of male orders, including the recruitment of new members, research, publication of religious literature, was deemed illegal, and thus punishable under law. In the period of normalisation, in contrast to the 1950s and 1960s, there were not hundreds of cases of arrests, interrogations and convictions but there were individual trials. Only in the case of the Franciscans during the Vir campaign in 1983, and during other campaigns against them within the republic were dozens of order members prosecuted, of whom only five were sentenced in the Czech lands. Many of the cases that were brought to trial, despite serious interest from the state security services, ended in failure or reversal. In the 1970s and 1980s, the Communist authorities refrained from the previously widespread practices of interning monks in camps or nationwide manhunts. This was caused mainly by the negative reaction of the national opposition as well as international protests and coverage of those cases in the Western mass media. The persecution of male orders and the trials of their members continued in Czechoslovakia throughout the entire period of the Communist regime, with the exception of late 1960s. Since 1950 until the fall of the regime in 1989, with the exception of the period of the so-called Prague Spring, the activities of male orders were deemed undesirable and illegal. The long-term objective of the Communist regime was the complete destruction of conventual life in Czechoslovakia and to convert the society to atheism.